Eco-Friendly Synthesis of Copper Oxide Nanoparticles Using Ephedra alata from El Oued: Comprehensive Protocols for Biological Applications - Ben abdallah Saber; Djebloun Ali; Logbi Oualid (. جامعة الوادي.Université d'EL-Oued., 2025)
The green synthesis of copper nanoparticles using Ephedra alata extract from the El Oued region represents a promising alternative to conventional costly chemical methods, as the biosynthesis approach is environmentally safe. In this study, the nanoparticles were characterized by FTIR spectroscopy, which revealed several functional groups involved in the stabilization of CuNPs, including hydroxyl (–OH) at 3200–3300 cm⁻¹, C–H at 2930 and 2850 cm⁻¹, carbonyl (C=O) at 1750 cm⁻¹, C=C at 1600 cm⁻¹, carboxylate (COO⁻) at 1400 cm⁻¹, C–N or C–O at 1310 cm⁻¹, ether or polysaccharide vibrations at 1010 cm⁻¹, and a sharp Cu–O bond peak at 600 cm⁻¹, which appeared clearly after calcination of the synthesized material, confirming the successful formation of CuNPs. XRD analysis also showed sharp diffraction peaks at 2θ angles of 38.89° and 35.69°, with corresponding intensities of 1586 and 1505, respectively, indicating the presence of CuO NPs rather than Cu₂O. Cytotoxicity testing showed complete cell death at 20 mg/mL, with an LC₅₀ value around 5 mg/mL. The synthesized nanoparticles exhibited promising biological activities, including anti-inflammatory effects reaching 98% at 2.5 g/mL, antibacterial activity against E. coli with an inhibition zone of 19 mm at 40 mg/mL, and antifungal effects against Saccharomyces cerevisiae with a similar zone of inhibition. The particles also showed notable inhibition of α-amylase starting at 10% at 5 µg/mL and exceeding 80% at 35 µg/mL, indicating potential antidiabetic applications. Furthermore, high antibiofilm activity was recorded, with inhibition rates of 69.64% for Bacillus and 67.45% for Salmonella typhimurium at the highest tested concentration (900 µg/mL). These findings confirm that the biosynthesis of copper nanoparticles using Ephedra alata is a promising strategy for developing nanomedical applications targeting bacteria, fungi, inflammation, and diabetes, while supporting the trend toward sustainable and eco-friendly nanotechnology.
Applied Biochemistry
Keywords: Copper nanoparticles; Green synthesis; Sustainable nanotechnology; Ephedra alata; Antifungal; Antibacterial; Anti-inflammatory; Antidiabetic; Antibiofilm.